MEKANISME PENGGUNAAN SEBAGIAN HAK PENGELOLAAN (HPL) BANDARA KUALA NAMU OLEH PIHAK KETIGA - YUHENI HASARIAH SIREGAR (PREMISE LAW JURNAL, 2016)
Right of Management is the Right of Use given by a nation which the implementation authority is delegated partially to the rights holder. The authority includes the right to use the land for the sake of a business and the authority of handover parts of the land to a third party. The need of land in order to increase a business activity is getting higher. Therefore, a right is needed to give high authority to the right holder to plan the allocation and use of land in question of his business growth.Legal guarantee is covering status, subject and object of right of management. The guarantee of legal protection covers the security of rights holders to use the land without geting any interference or claim from other parties. This research aimed to know the implementation of the release of right of use space which was Kuala Namu International Airport’s right of management to the third party by PT. ANGKASA PURA II. This research used descriptive analytical method with juridical approach by collecting the data related to the problems in PT. ANGKASA PURA II. Keywords: Right of Management, Mechanism, Third Party